Towards understanding the gliotoxin detoxification mechanism: in vivo thiomethylation protects yeast from gliotoxin cytotoxicity - Elizabeth B. Smith; Stephen K. Dolan; David A. Fitzpatrick; Sean Doyle; Gary W. Jones (Microbial Cell)
Gliotoxin (GT) is a mycotoxin produced by some species of ascomycete fungi including the opportunistic human pathogen Aspergillus fumigatus. In order to produce GT the host organism needs to have evolved a self-protection mechanism. GT contains a redox-cycling disulfide bridge that is important in mediating toxicity. Recently is has been demonstrated that A. fumigatus possesses a novel thiomethyltransferase protein called GtmA that has the ability to thiomethylate GT in vivo, which aids the organism in regulating GT biosynthesis. It has been suggested that thiomethylation of GT and similar sulfur-containing toxins may play a role in providing self-protection in host organisms. In this work we have engineered Saccharomyces cerevisiae, a GT-naïve organism, to express A. fumigatus GtmA. We demonstrate that GtmA can readily thiomethylate GT in yeast, which results in protection of the organism from exogenous GT. Our work has implications for understanding the evolution of GT self-protection mechanisms in organisms that are GT producers and non-producers.